Hands-on laboratory activities: Enhancing conceptual understanding and developing practical skills of students - Marinel Agravante-Destacamento (University of Muhammadiyah Malang, 2025)
This research assessed the effectiveness of developed hands-on laboratory activities on the academic performance and skill development focusing on cell transport mechanisms. A concurrent mixed-methods, quasi-experimental research design was employed, comparing an experimental group that used hands-on activities with a control group that used a conventional teaching setup. Participants were Grade 11 STEM students from a science high school in Cebu. The primary quantitative instrument was a validated 20-item multiple-choice pretest and posttest (Cronbach’s α = 0.718). Quantitative data were analyzed using dependent- and independent-samples t-tests. Qualitative data were gathered via individual interviews with selected students and subjected to thematic analysis. Pretest results showed that both the control (41.00%) and experimental (38.00%) groups initially did not meet expectations. Posttest results revealed a marked difference: the experimental group achieved an overall mean score of 91.00% (outstanding), while the control group remained below the satisfactory threshold (64.50%). A comparison of mean gains demonstrated a statistically significant difference in favor of the experimental group (t=6.25, p=.001), with a mean increase of 10.63 compared to the control group's 4.73. Furthermore, the hands-on approach was the only method that produced statistically significant knowledge gains across all tested competencies, including endocytosis/exocytosis (p=.001). Qualitative themes supported these results, highlighting the positive impact of the activities on the development of practical skills, collaboration, and long-term memory through visualization and active recall. The hands-on laboratory activities, is highly effective at fostering conceptual mastery and developing essential practical skills. It is strongly recommended for integration into the senior high school biology curriculum, serving as a basis for developing localized, context-specific teaching materials that promote active, experiential learning.